2003
DOI: 10.1088/1464-4266/5/3/385
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quantum dynamics in an open many-body system: transition to superradiance

Abstract: Abstract. We study the dynamics of a complex open quantum many-body system. The coupling to external degrees of freedom can be viewed as a coupling to a radiation field, to continuum states or to a measuring apparatus. This perturbation is treated in terms of an effective non-Hermitian Hamiltonian. The influence of such coupling on the properties of the many-body dynamics is discussed, with emphasis on new effects related to dynamical segregation of fast and slow decays and the phase transition to Dicke superr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The N − 1 degenerate mutual orthogonal stationary states with the energy E = Ω are given by the wave functions (7) with N − 1 conditions N n=1 c m n = 0. The collective state (9), which we call a single photon Dicke state [7], is formed by a single photon, which propagates through the N qubit chain. Therefore, under this condition, the state (9) decays with a rate which is N times faster than the rate of the spontaneous emission of a single qubit.…”
Section: Collective States Of Disordered N-qubit Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…The N − 1 degenerate mutual orthogonal stationary states with the energy E = Ω are given by the wave functions (7) with N − 1 conditions N n=1 c m n = 0. The collective state (9), which we call a single photon Dicke state [7], is formed by a single photon, which propagates through the N qubit chain. Therefore, under this condition, the state (9) decays with a rate which is N times faster than the rate of the spontaneous emission of a single qubit.…”
Section: Collective States Of Disordered N-qubit Chainmentioning
confidence: 99%
“…We show that the widths of two resonances experience the repulsion in a narrow range of ∆Ω near zero. The effect of repulsion of resonance widths in open systems is known for a long time [8,9]. Due to this effect the impurity atom gives rise to the enhancement of the rate of superradiance emitted by assembly of N qubits.…”
Section: A Calculation Of the Energy Spectrummentioning
confidence: 99%
“…Below we only briefly outline the theoretical basis of the approach; the detailed study, however, can be found in the textbook [6,7], and the previous development of the method was reviewed by Rotter [8]. Although nuclear physics is the main application arena to be discussed in this paper, the method is actively utilized in diverse areas [5] from molecular and condensed matter physics [9] to multi-quark systems [10].…”
Section: Continuum Shell Modelmentioning
confidence: 99%
“…The latter set of states are seen in figure returning back to the real axis. The details of this phase transition are discussed in [9,15,16].…”
Section: Super-radiancementioning
confidence: 99%
“…This is an area in which the conventional division of nuclear physics into "structure" and "reactions" becomes inappropriate and two views of the process, from the inside (structure and properties of bound states) and from the outside (cross sections of reactions), have to be unified. The effective Hamiltonian of a compound nucleus with open decay channels has the form: 33 …”
Section: Quantum Engineering With Heavy Nuclei: Connection With Electmentioning
confidence: 99%